A Stranger at Fellsworth - Ladd, Sarah E. (Nashville : Thomas Nelson, 2017)
"Sara Ladd delivers another delightful romance in her newest novel, A Stranger at Fellsworth. Filled with an air of mystery and historical charm, this story will keep readers coming back for"--
Keywords: Poachers -- Fiction; Widowers -- Fiction; Christian fiction; Love stories